2018
DOI: 10.1177/0972150918811519
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Preference on Imported and Locally Made Furniture in Dar es Salaam and Arusha, Tanzania

Abstract: This study was designed to assess the consumer’s preference between imported and locally made furniture in Dar es Salaam and Arusha in Tanzania. Primary and secondary data for the study were collected from furniture consumers in the study area. A total of 134 consumers were surveyed. Questionnaires and documentary reviews were used for data collection. Descriptive statistics and binary logistic regression were used in the analysis of data. The result of the study revealed significant differences on the levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Therefore, H A was accepted, and it was concluded that access to network programmes could positively influence the performance of exporting handicrafts MSEs in Tanzania. These findings corroborate those of Cisi et al (2016), Kumburu (2016), Surin and Wahab (2013) and Gronum (2015), who observed a positive and significant link between networking and SMEs' performances.…”
Section: Performance Of Handicrafts-exporting Msessupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, H A was accepted, and it was concluded that access to network programmes could positively influence the performance of exporting handicrafts MSEs in Tanzania. These findings corroborate those of Cisi et al (2016), Kumburu (2016), Surin and Wahab (2013) and Gronum (2015), who observed a positive and significant link between networking and SMEs' performances.…”
Section: Performance Of Handicrafts-exporting Msessupporting
confidence: 91%
“…Such restrained MSEs, if left with no network, more often than not will steadily underperform in the foreign markets. Studies (i.e., Kumburu, 2016;Gronum, 2015;Ayako et al, 2014;Surin & Wahab, 2013) have shown that MSEs with no access to networks linkages are more likely to underperform. This underperformance is a serious matter that involves a serious waste of profitability, manufactured exports, human resources, GDP and government revenues.…”
Section: Objective and Rationale Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…During analysis, researchers tried to understand respondent’s views from case studies and observation and interpreted them (Mashenene, 2016). The explanations and observations were matched with the literature and empirical evidence elsewhere (Kumburu & Kessy, 2018).…”
Section: Analytical Modelmentioning
confidence: 99%
“…In addition, the effect levels of the factors vary according to marital status and education level.The results obtained from this research will be useful in making managerial decisions about marketing. groups, local furniture was preferred because of its cheapness (Kumburu & Kessy, 2021). In a study in Finland, focusing on the development of marketing strategies by going to market segmentation depending on the differences in the constructions of wooden home furniture, quality and design are the most important features in all market segments, while style and advertising are determined as the last attributes (Pakarinen & Asikainen, 2001).…”
mentioning
confidence: 99%